AGENCY AND AWARENESS. (14th September 2012) - Andreou, Chrisoula
Abstract I focus on the idea that if, as a result of lacking any conscious goal related to X‐ing and any conscious anticipation or awareness of X‐ing, one could sincerely reply to the question 'Why are you X‐ing?' with 'I didn't realize I was doing that, ' then one's X‐ing is not intentional. My interest is in the idea interpreted as philosophically substantial (rather than merely stipulative) and as linked to the familiar view that there is a major difference, relative to the exercise of agential control, between acting on a conscious goal (even one the agent is not actively thinking about) and acting on a non‐conscious goal (about which the sincerely 'clueless' response 'I didn't realize I was doing that' could be provided). After raising some doubts about the target idea, I consider the two most promising lines of defence. I argue that neither is convincing, and that we should reject the suggestion that the idea is properly accepted as a matter of common sense. Even absent any conscious goal related to X‐ing and any conscious anticipation or awareness of X‐ing, there is room for counting X‐ing as intentional if X‐ing is, or is appropriately related to, a non‐conscious goal.